ANALISIS SEMIOTIKA TERHADAP KEANEKARAGAMAN MOTIF BATIK PEKALONGAN HASIL AKULTURASI BUDAYA: Semiotic Analysis Of The Diversity Of Pekalongan Batik Motifs Resulting From Cultural Acculturation - Dewinta Sari Rahmaputri (Jurnal Dimensi Seni Rupa dan Desain, 2023)
Pekalongan City, located in Central Java, is known as the World's City of Batik because almost most of its people's economy is grown by the batik industry. In its journey, the diversity of Pekalongan Batik motifs comes from the results of cultural acculturation, including Indian, Arabic, Dutch, Peranakan Chinese, and Japanese. This cultural acculturation process can occur because Pekalongan City is located on the North Coast of Java, which has become an inter-island trade traffic in the archipelago. Semiotics aims to interpret the meaning contained in a sign. The method used is the semiotic approach by Charles Sanders Pierce through the Triangle of Meaning Theory which explores how meaning arises from a sign when the sign is used to communicate. The purpose of this research is to examine some of the iconic motifs of Pekalongan Batik resulting from the process of cultural acculturation in which each object has a meaning or meaning drawn from a sign. Keywords: Semiotics, Motif, Pekalongan Batik, Acculturation, Meaning